Rozwiąż równania
3(x-2)+16=2(x-4)
2(x-5)+6 = 2x+4
4x-(2x-2) = 2(x-7)
proszę o zrobienie do 17:00



Odpowiedź :

Odpowiedź:

3( x-2)+16 = 2( x-4)

  3x -6 +16= 2x -8

   3x-2x= -8 -16+6

       x= -18

spr...     3*(-18) -6+16 =2*(-18) -8

    -54 -6+16 = - 36 -8

               -44 = -44

                    L=P

2( x-5) +6 = 2x+4

   2x -10 +6= 2x+4

    2x-2x= 4 +10-6

           0≠ 8

          L≠P

  równanie sprzeczne

4x-( 2x-2) = 2( x-7)

  4x-2x +2=   2x -14

  4x-2x-2x= -14 -2

       4x-4x ≠ -16

          0≠ -16

           L≠P

równanie sprzeczne

Szczegółowe wyjaśnienie:

Mam nadzieje ze pomogłam
Zobacz obrazek Gabi567188